Platform lobbying: Policy influence strategies and the EU's Digital Services Act - Robert Gorwa; Grzegorz Lechowski; Daniel Schneiß (Internet Policy Review, 2024)
This paper examines how platform companies seek to lobby and otherwise influence policymakers during heated regulatory episodes. While there has been some valuable recent work on different policy influence strategies deployed by platform firms, in particular the emerging use of "user-facing" tactics of consumer mobilisation, current research tends to neglect the role of specific institutional contexts and related power structures intermediating the exertion of business power. Developing an institutionally situated approach, we offer an analysis of platform policy influence during the Digital Services Act (DSA) negotiations in the EU from 2019-2022. Through an analysis of political science literature on business power and interest group politics, we outline five strategies of corporate policy influence (access lobbying, coalition building, stakeholder mobilisation, public relations, and funding). Drawing on freedom of information requests, the EU Transparency register, and civil society watchdog reporting, we then provide an analysis of how platform firms sought to influence EU policymakers through these strategies around the DSA.
Keywords: 300; Platform power; Lobbying; Business power; Policy influence; Platform governance